A Practical Method for p-Methoxybenzylation of Hydroxy Groups Using 2,4,6-Tris(p-methoxybenzyloxy)-1,3,5-triazine (TriBOT-PM) - Yamada, Kohei; Fujita, Hikaru; Kitamura, Masanori; Kunishima, Munetaka (Synthesis, 2013)
A new acid-catalyzed p-methoxybenzylating reagent, 2,4,6-tris(p-methoxybenzyloxy)-1,3,5-triazine (TriBOT-PM), has been developed. The reaction of acid- and alkali-labile alcohols with TriBOT-PM in the presence of a catalytic amount of various acids (TfOH, BF3·OEt2, CSA, etc.) afforded the corresponding p-methoxybenzyl ethers in good yields. Since TriBOT-PM is an air-stable crystalline solid and can be prepared from inexpensive materials, i.e. cyanuric chloride and anisyl alcohol, this route is of practical use.
Keywords: benzylation; protecting groups; cations; ethers; alkylation